'The human toll': Highlighting the unacknowledged harms of prison suicide which radiate across stakeholder groups. Issue 2 (July 2022) - Banwell-Moore, Rebecca; Tomczak, Philippa; Wainwright, Lucy; Traynor, Catherine; Hyde, Sara
Internationally, prisoner mortality rates are up to 50% above those in the community. Although prisoner deaths are frequent and have significant implications across a broad range of stakeholder groups, these harms are rarely acknowledged. We address this by presenting original data from semi-structured interviews with 19 senior Prison Service staff (representing 8 prisons and 11 regions) and 16 Ombudsman investigators in England and Wales. These professional groups have received limited consideration in previous research. Without negating implications for bereaved families and other prisoners, we demonstrate that scholars have grasped neither the impacts of prisoner deaths on investigators, nor the extent of the harms experienced through investigations. All stakeholders benefit from reducing prisoner suicides, but death investigations do not enable stakeholders' 'shared ground' to be mobilised. Currently, death investigations compound the harms of deaths.